Research on the Strength Prediction Model of Softened Mudstone Based on Triaxial Compressive Test of Rock - Kai Yun; Yongquan Zhu; Renyuan Wang; Zhichun Fang (Advances in Materials Science and Engineering)
Mudstone is highly sensitive to water. When it comes into contact with water, the softening phenomena such as the decrease of strength and the increase of deformation are prominent. It is of great significance to clarify its related mechanical properties. For the tertiary mudstone, a triaxial compression test and a Brazilian splitting test are carried out under the conditions of four kinds of water content (0, 10.1%, 12.5%, and 14.1%) and four kinds of confining pressures (0 MPa, 2 MPa, 5 Mpa, and 10 MPa). The test results show that (1) with the increase of confining pressure and water content, the mudstone changes from brittle failure to ductile failure. The higher the confining pressure, the greater the strength and elastic modulus. The higher the water content, the significantly lower the strength and elastic modulus, and the higher the strain. (2) With the increase of water content, the influence of confining pressure on strength is more prominent. High confining pressure can effectively inhibit the trend of strength attenuation. (3) When the water content is low (0–10.1%), the strength of the mudstone is mainly related to its own water content. When the water content increases to 10.1%–14.1%, both the confining pressure and the water content are important factors affecting the strength of the mudstone. Then, the applicability of five commonly used strength criteria to the strength prediction of softened mudstone is compared and analyzed. The results show that the Rocker strength criterion can more accurately and conveniently predict the strength of mudstone under different water content. Finally, based on this strength criterion, a nonlinear strength prediction model of softened mudstone considering water content and confining pressure effect is proposed and its good applicability is verified.